Analisa Debit Banjir Menggunakan EPA Storm Water Management Model (SWMM) Di Sub DAS Kampar Kiri (Studi Kasus: Desa Lipat Kain, Kampar Kiri) - Robby Aulia Syuhada; Yohanna Lilis Handayani; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Flood occurs when the water discharge exceeds the capacity of the river, which may harm impact of flooding in municipal area. This research aims to test the reliability of EPA SWMM software in rural area and compare it with the discharge from HEC-HMS. The reliability of the softwares was determined by calculating the difference in discharge error (DE). The simulation was performed by using flood discharge with 5 and 25 years of return period. Based on the test results, the EPA SWMM 5.0 software has good reliability with the calculated DE value less than 5% (2,593% for 5 years-return period and 2,268% for 25 years-return period). For HEC-HMS software, the DE is calculated as 1,196% for 5 years-period discharge and 2,072% for 25 years-period discharge. Therefore, it can be concluded that the HEC-HMS software has better accuracy than the EPA SWMM softwareresidential and agriculture areas.Keywords : Flood discharge, EPA SWMM 5.0, correction difference discharge